Identification and Characterization of Two Thrombin-activatable Fibrinolysis Inhibitor Isoforms - Zhao, Lei; Morser, John; Bajzar, Laszlo; Nesheim, Michael; Nagashima, Mariko (Thrombosis and Haemostasis, 1998)
Thrombin-activatable fibrinolysis inhibitor (TAFI) is synthesized by the liver and is thought to circulate in plasma as a plasminogen-bound zymogen. When it is activated by the thrombin/thrombomodulin complex, activated TAFI exhibits carboxypeptidase B-like activity. To study the structure-function relationship of TAFI, we expressed recombinant human TAFI in insect cells. During the cloning of TAFI cDNA from several human liver cDNA libraries, we identified a second TAFI cDNA which differed from the published sequence at 2 positions. One of these sequences resulted in a substitution of alanine for threonine at residue 147, the other was a silent mutation. These substitutions were found in several cDNA libraries from different sources. Using Southern blot analysis, we confirmed the existence of this TAFI polymorphism in the population. In order to compare the activation and activity of TAFI isoforms, we expressed both isoforms in the baculovirus expression system, and compared the enzyme kinetics of the purified proteins. The molecular weight of recombinant TAFI is lower than plasma TAFI due to differences in glycosylation. The two recombinant TAFI iso-forms had similar activation kinetics and the activated enzymes had similar carboxypeptidase B-like activity towards small molecule substrates. Their ability to retard clot lysis was found to be similar in a plate clot lysis assay.